Um “operário das palavras” em seu labirinto: a participação de Guillermo Cabrera Infante na Revolução Cubana, memórias desde o exílio - Favatto, Barthon (2014)
The present article is a critical effort to summarize and report the results of a study, carried out in order to obtain a master's degree from the Departamento de História of UNESP/Faculdade de Ciências e Letras de Assis. On the following pages, we present and discuss the engagement of Guillermo Cabrera Infante during the revolutionary process in Cuba, which occurred between 1956 and 1959. The starting point is a historicized reading of the autobiography Cuerpos Divinos, published in 2010, five years after the death of the author, who had lived four decades in the exile.